The Final Stage of Mongol Invasion of Europe: A Military Force and Secret Diplomacy (2) » - A.V. Mayorov (Золотоордынское обозрение)
The paper analyzes the sources of information on the direct contact of the Emperor Frederick II with the Mongols before the attack of the latter on Europe, the persistent rumors of his collusion with the invaders, who came to blow mainly to the enemies of Frederick, the refusal of the Emperor of an armed clash with the Tatars, the refusal to participate in the Crusade prepared by the German prelates against the Tatars, but instead – a withdrawal of the imperial troops in Italy and the siege of Rome in order to force the pope to recognize the supremacy of the Emperor, the sudden retreat of the Tartars themselves from the German border and the abandonment of the original plans for the conquest of Germany, unexpected counteraction against Frederick of the German prelates who had been previously loyal to the Emperor and who accused him of a serious crime against the Church and the whole of Christianity. The author concludes that the Emperor Frederick and the leaders of the Western Mongol campaign were associated with secret mutual obligations. Many of his contemporaries were aware of the Emperor’s secret contacts with the Tartars (Albert von Beheim, Matthew Paris, and others.). The author analyzes the information and is trying to separate the elements of political propaganda from the established facts. The Emperor’s conspiracy with the Tatar leaders is indicated both by direct evidence and numerous indirect information analyzed in the article. On the one hand, the Emperor did everything possible to avoid a direct military confrontation with the Tatars and disrupt plans of his supporters in Germany to combat the invaders. On the other hand, the Tatar impact in Europe fell entirely on the Frederick’s enemies who took the side of the pope in the latter’s conflict with Emperor. As a result of the Tatar invasion of Europe position of the Emperor in his confrontation with the Roman church greatly strengthened. This change in the balance of power obviously angered the church prelates and the subsequent rebellion of the German Bishops against Frederick provoked long civil war in Germany.